Wood walls insulated with coconut fiber [Muro de madera aislado con fibra de coco] (2019)
Solid wood gives the shape to walls, while panels are the coating and they are nailed or screwed to the wood sections. In the cavities between the wood elements and the panels, a thermal and acoustic insulator must be added. Unfortunately, almost all of the currently used insulators (mineral wool, expanded polystyrene, polyurethane) are not biodegradable and require the use of vapor barriers (polyethylene sheets, aluminum foils, etc.) that deteriorate rapidly and that are relatively environmentally unfriendly. In this article, the use of coconut fiber instead of conventional insulators is suggested. The acoustic absorption and thermal conductivity coefficients of composite sections taken from wood walls with coconut fiber are estimated. In this way, good thermo-acoustic conditions inside the wood building are achieved using an ecological insulating material. © The author; licensee Universidad Nacional de Colombia.